CCMUG : a model for the development of mobile and ubiquitous games focused on chronic diseases - Sá, Kévin Cardoso de (2018)
Chronic diseases are the main cause of mortality in the last few decades, accounting for 59% of all deaths in the world. It is possible to prevent the development of such diseases using tools and methods that instruct the population. One way to achieve this goal is by using games, since they make it possible to teach subjects to the users, without them actively knowing that they are learning new concepts. Through a mapping study, it was possible to identify existing works that employ games focused on chronic conditions, however these works cover a reduced range of these conditions, are mainly targeted towards a younger audience and the majority is of a specific genre, exergames. In this context, this work proposes a model, named CCMUG, for the development of mobile and ubiquitous games that address chronic diseases. The contribution of our work is the definition of a model for the development of games for awareness focused on chronic diseases, subdividing the model into components with relationships between them. Unlike the related work considered, there are no restrictions regarding the type of game target audience and chronic disease addressed. The model aids in the development of games of the most varied genres, for different chronic conditions and individuals of all ages. We conceived the design and developed a mobile game focused on HIV/AIDS, based on the model proposed in this work. We then conducted a individual evaluation with a group of Digital Games undergraduate students of Universidade do Vale do Rio dos Sinos (Unisinos), with the objective to qualify the design of the game. The results obtained show that the game assumes its role of entertaining the players and teaching them concepts regarding the chronic condition. Furthermore, we identified aspects of the design to be improved in the development of the game prototype. Afterwards, we conducted a second evaluation, employing the focus group methodology, with a group of six students who participated in the first evaluation. The aim of this evaluation was to identify if a narrative should be used in the game and, if so, how it should be designed. The participants agreed that the use of a narrative would be beneficial in a game that tries to teach new concepts to the players, but it should be well elaborated. Through the focus group, we conceived a narrative for the game as well as additional features originated from the story. Then, we conducted an evaluation on the prototype after its development to assess the user enjoyment of the game. It was based on a modified version of EGameFlow, a survey that serves as a scale of measurement of the enjoyment and fun of the users in e-learning games. EGameFlow is divided in several dimensions that are assessed with the mean and standard deviation of the answers of the participants. The participants played the game and answered the questionnaire. Overall, all dimensions scored satisfactorily, showing that the prototype is considered to be fun and enjoyable for the players. The last evaluation of this work gathered opinions of game developers to ascertain the validity of our model, its components and relations for developing games focused on chronic conditions. This step occurred as a individual structured interview that followed a explanation of the proposed model and the developed prototype. There were no requests to remove, add or drastically change any component of our model, only minor corrections were applied. Overall, the results are positive and all developers fully agree that our model can be used to develop games, mobile or ubiquitous, focused on chronic conditions without the restrictions identified in the related works. The results confirm that CCMUG can be used as a guideline to develop games in this context. However, more evaluations with different prototypes focusing on other chronic diseases are planned as future works.